Post-Operative Neurological Complication after Congenital Heart Surgery (ASD, VSD, TOF) Operation in Pediatric Patients at Bangladesh Shishu Hospital - Al-Amin, Dewan Md; Sultana, Shadaka; Jamal, Janifa; Chowdhury, Tasfia Mahmood; Tarik, Khalifa Mahmud; Hossain, Mohammad Makbul (Journal of Brahmanbaria Medical College, 2026)
Background: Congenital Heart Disease (CHD) is becoming more frequently identified, which could be attributed to improvements in diagnostic technologies and the availability of skilled labour. There is a lack of information on the aetiology and outcome of the numerous research that have been carried out in Bangladesh to determine the prevalence and pattern of CHD. To examine the post-operative neurological consequence following Congenital Heart Surgery. Materials and methods: It was a cross-sectional study conducted in cardiac intensive care unit, Bangladesh Shishu Hospital between June 2021 and June 2024.The data of all children less than 15 years old of either gender who underwent open-heart surgery for congenital heart defects, admitted in cardiac intensive care unit and had CT brain secondary to CNS insult were extracted from hospital record. Children who had bleeding disorder and normal Glasgow coma scale 15/15 were excluded. EEG is done for the patients who had clinical seizures, and its nor routinely done for all patients. Results: Most common neurological complication was seizure (11.63%) followed by late consciousness 9.30% and absent brain stem reflexes 2.33%, abnormal movement 4.65%, epilepsy 2.33% and Behavioral changes 3.26% respectively. Figure II shows mortality was found 14(4%). The children with neurological complication after surgery had significantly longer ICU stay (p=0.006) hospital stay (p=0.04), mortality after surgery (p=0.002). Conclusion: The most prevalent neurological complications were seizure, late consciousness, absent brainstem reflexes, aberrant movement, epilepsy and behavioural abnormalities. Children who experienced neurological complications following surgery had considerably higher ICU stays, hospital stays and mortality rates. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 12-15